Conceivable Of Online Learning: A Perspective From The Quantity Surveying Education In Malaysia - Vinod Thiren, Theva Thason (Universiti Malaysia Sarawak, (UNIMAS), 2023)
The most recent COVID-19 epidemic has unquestionably brought to light the increased significance of online learning in the field of education. Despite this, a significant number of educators from the QS department continue to be reluctant to carry out online classes after the Covid 19 pandemic. Hence, the objective of this research is to determine the possible advantages of adopting online learning in Quantity Surveying education in Malaysia. At the same time, the purpose of this research is examine the major obstacles in adopting online learning and to determine the significant strategies to overcome the obstacles in adopting online learning in Quantity Surveying education in Malaysia. Hence, qualitative approach has been adopted in this research by carrying out the semi-structure interview among three (3) QS educators from the top management of Quantity Surveying Department from the FBE, UNIMAS. Content of analysis is being used to analyse the data collected. The findings from this study reveals that all top management educators of QS education such as the Head of QS Department, the Deputy Dean of QS Department and the Programme Coordinator of QS Department have showed their positive response on the potential advantages of online learning in QS education such as optimizing the lecturers and students time and also reduce the cost on education. The respondents have faced their respective obstacles in adopting online learning in QS education. For instance, accreditation problem, greater initial time of investment by the educators and the social interaction and concern for quality. The significant strategies are providing faculty with technical support, training for students and lecturers and also proper planning by the educators. In addition, this study uncovered the possibilities and willingness of the QS department to perceive or implement fully online courses in QS education in Malaysia.